Level of awareness of HIV/AIDS pandemic among undergraduate students of the university of Ibadan (2012)
The study assessed the level of awareness of students of the University of Ibadan about HIV/AIDS, and the effective preventive strategies the students know that can reduce the further spread of HIV/AIDS, and suggest ways to cultivate the right attitudes concerning issues relating to AIDS in order to make the University of Ibadan an AIDS-free institution, and to make recommendations on how students can be involved in reducing the spread of HIV/AIDS. This study employed descriptive research design in which information was obtained from an observed population and questionnaires were used as the research instrument. The result of the findings have shown that a very good number of students are aware of the issue of HIV/AIDS, its signs and symptoms, its mode of transmission and various preventive strategies that could curtail the spread of AIDS, although a few students are still doubting the reality of HIV/ADS. The roles of social workers and prevention as well as curbing the spread of HIV/AIDS were recommended.